Pengaruh Pengambilan Keputusan Terhadap Kepuasan Kerja Peternak Ayam Ras Pedaging Mitra PT. X (International Forum of Researchers and Lecturers, 2023)
This research was to determine the influence of decision-making factors for broiler farmer joining as partners with PT. X on farmer job-satisfaction. The research was conducted from 20 February to 20 March 2023 at farms of partners PT. X. The research sample consisted of 32 farmers as partner of PT. X. The methods used in this research were quantitative. Data were analyzed by using a Multiple Regression Analysis. The results showed that information factor variable had a significant influence on the satisfaction of farmers who had joined as partners with PT. X. However, other variables such as personality, coping, and culture did not have a significant influence on farmer satisfaction. The simultaneous influence of the variables, including the information factor, personality, coping, and culture, on farmer satisfaction was 24.9%, while the remaining 75.1% was influenced by other variables.